Fatherless Phenomenon After Divorce and Its Impact on Children's Social and Academic Behavior - Mahendra, Juandra Prisma; Rahayu, Fitriani (Peneliti.net, 2024)
Fatherless is a term that refers to a condition when a child does not have the presence, care, or role of a father. One of the causes of fatherlessness is caused by divorce, which results in the child being separated from their father. The absence of the father's role can have a negative impact on children. One of them is in terms of academic and social skills. This study aims to determine the impact of the fatherless phenomenon after divorce on the behavior and academic abilities of children aged 5-11 years in one of the sub-districts in North Lombok Regency. This research is a type of qualitative research with the number of respondents in this study were 8 mothers. The results of the research in terms of the behavior of children who experience fatherlessness are that children do not have attachment to their fathers, children's independence is not optimal, and children's emotional control is still low. Meanwhile, in terms of academic ability, children who experience fatherlessness are children who cannot focus on learning due to negative emotions such as shame, anger, and low self-control. Children who experience fatherlessness also experience failure in subjects and have low motivation to learn. Children who feel loss and severe disappointment psychologically towards the role of the father then result in a decrease in learning achievement at school. So it is necessary to do socialization to parents to provide an understanding of the importance of the father's role in parenting.